Daily Reflections for Highly Effective Teens - Covey, Sean (New York Fireside Rockefeller Centre, 1999)
Presents daily meditations designed to inspire and motivate teenagers.
Keywords: Teenagers--Conduct of Life -- Self-help Techniques for Teenagers -- Spiritual Life